The Impact of Trans Sumatera Toll Road Development on The National Road in Palembang City - Perwira Manggala Wicaksana; Erika Buchari; Melawaty Agustien (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2022)
The toll road network in Indonesia is growing very rapidly in line with the plan of the Government of the Republic of Indonesia to build 24 toll roads on the island of Sumatra which will connect every provincial capital. The impact of toll road construction is certainly different in each region, and those who feel the greatest impact in the areas closest to them. Toll roads, both existing and planned, cause the development of local roads in the vicinity directly or indirectly. Development of road network systems can affect the movement so that network performance becomes better and increasing road capacity is not the right solution to overcome congestion on the road. This study discusses the impact of the construction of the Trans Sumatra toll road on the national road network in the city of Palembang by using four-step models and a macro simulation program, namely the software PTV Visum. The model reliability test resulted in a determinant coefficient (R2) of 0.7227, which means it represents the existing traffic conditions in the field. The modeling stage is continued to predict the performance of the road network after the Trans Sumatra Toll Road operates. Prediction results show in 2036 there will be a decrease in the level of service with the increase in the V/C Ratio of National Roads that directly access the Trans Sumatra Toll Road. Adding more traffic lanes in 2031 and 2036 on these roads, will significantly improve the performance of the National Road network. The unification of the Trans Sumatra toll gate also helps to increase the level of service on the nearest road.